Salma the Syrian chef - Ramadan, Ahmad Danny; Ramadan, Ahmad Danny (Annick Press, 2020)
"Newcomer Salma and friends cook up a heartwarming dish to cheer up Mama. All Salma wants is to make her mama smile again. Between English classes, job interviews, and missing Papa back in Syria, Mama always seems busy or sad. A homemade Syrian meal might cheer her up, but Salma doesn't know the recipe, or what to call the vegetables in English, or where to find the right spices! Luckily, the staff and other newcomers at the Welcome Center are happy to lend a hand--and a sprinkle of sumac. With creativity, determination, and charm, Salma brings her new friends together to show Mama that even though things aren't perfect, there is cause for hope and celebration. Syrian culture is beautifully represented through the meal Salma prepares and Anna Bron's vibrant illustrations, while the diverse cast of characters speaks to the power of cultivating community in challenging circumstances."--